Strategi Bauran Pemasaran 7P Menggunakan Pendekatan Analisis SWOT dalam Upaya Meningkatkan Daya Saing Mangata Coffee & Eatery - Rochmadika, Hanif; Parantika, Asep (Media Wisata, 2023)
This research was conducted on Mangata Coffee & Eatery, a culinary business. This study aims to determine and analyze the application of the 7P marketing mix strategy based on a SWOT analysis of Mangata Coffee &; eatery. The results of the SWOT analysis method are used as guidelines to determine alternative strategies for the 7P marketing mix that can be used by Mangata Coffee & Eatery. The research method uses a type of qualitative research with descriptive analysis that refers to the 7P marketing mix, namely Product, Price, Promotion, Place, Process, people, and Physical Evidence. Data collection techniques are carried out by means of interviews, observation, and documentation. The analysis method used is the SWOT analysis method with stages of identifying the 7P marketing mix, then compiling the IFAS and EFAS matrices, determining nine-cell diagrams, and creating alternative strategies from the SWOT matrix. The study results concluded that Mangata Coffee & Eatery was in the V-cell diagram position, resulting in two strategies: maintaining the market and improving products.